Human Midbrain Participates In Mismatch Detection Without Cognitive Activity Of The Cerebral Cortex: Case Report - Kantserova, Anna O.; Oknina, Lyubov B.; Masherov, Eugeny L.; Podlepich3, Vitaly V.; Zaitsev, Oleg S.; Pitskhelauri, David I. (Archives of Clinical and Biomedical Research, 2019)
Mismatch detection is the process of identification of rare stimuli from a sequence of stimuli. This important cognitive function is usually attributed to the cerebral cortex. To test the human midbrain involvement in sound mismatch detection, we recorded local field potentials in the states of deep anesthesia and clear consciousness from the drainage-electrode implanted in the cerebral aqueduct of an adult patient with an obstructive hydrocephaly who had undergone pineal region tumor removal through anterior interhemispheric transcallosal approach. We found a significant difference in the state of deep anesthesia at 256-364 ms after hearing a rarely presented sounds compared with frequently presented sounds and equally probable sounds. This difference was not found in the same experiment in the state of clear consciousness. The results suggest that human midbrain participates in mismatch detection and can do it even without cognitive activity of the cerebral cortex. Amplitude-frequency analysis of the midbrain records revealed that propofol affects the electrical activity of both human midbrain and cortex but the level of inhibition of the cortex is 6 times higher than the level of inhibition of the midbrain. We suppose that the human cortex is more susceptible to propofol than the human midbrain.